Partial Replacement of Cement with Sugarcane Waste Ash in Cement Concrete. - Muhindo, Martin (Kabale University, 2023)
The entire construction industry is in search of a suitable and effective waste product that would considerably be used in concrete. Different types of waste materials and industrial by-products such as recycled concrete aggregate, plastics, glass, ceramic, fly ash, slag, sugarcane bagasse ash, rice husk ash etc., are being used with and without natural aggregates and ordinary Portland Cement (OPC). However, SCBA obtained by burning sugarcane bagasse possesses pozzolanic properties capable of improving the strength of concrete. This Research was therefore experimentally done to determine the effect of the addition of SCBA on the compressive strength of concrete as partial replacement for cement. ) SCBA was obtained by burning of the Sugarcane bagasse in furnace at DGAL. The bagasse was bought from jinja. They were burnt at a temperature of about 600°c to 700°c hence more amorphous form was obtained. The Ash was then grinded using a mortar and pestle and then sieved to remove impurities. The chemical and physical properties of the ash were determined. The combined percentage of silica, alumina, and Iron Oxide in the ash was 84.75% which is more than the 70%wt as stated in the ASTM C618 hence meeting the specifications. The ash was then added in concrete in percentages of 5%, 10%, 15% and 20% by the weight of cement in the mix of 1:2:3 Different physical tests were carried out on the materials that were used i.e., Sand, coarse aggregates and ash which include final and Initial setting time of cement blended.with ash, slump test on fresh concrete and compressive strength test on hardened concrete at different ages of 7, 14 and 28 days of curing. The slump of the Concrete on addition of the ash reduced considerably with the increasing percentage of SCBA as compared to the control experiment. The Compressive strength of concrete increased slightly with the addition of rice husk ash as compared to the compressive strength of the control experiment. The Bulk density also decreased with the increase in percentages of ash as compared to the control experiment as observed from the data sheets. In conclusion, Sugar Cane Bagasse Ash can be partially replaced in concrete up to 15% since the value obtained at 20% was below the minimum required for C25.